Caracterização das formas juvenis e adultas dos camarões-rosa Farfantepenaeus brasiliensis (Latrelle, 1917) e F. paulensis (Perez-Farfante, 1967) (Decapoda: Penaeidae) por meio de técnicas moleculares e morfologia comparativa - Teodoro, Sarah de Souza Alves [UNESP] (2014)
The greatest difficulty in identifying the pink shrimps Farfantepenaeus brasiliensis and F. paulensis occurs mainly in the juvenile stage, when secondary sexual characters are still in formation and the only way to separate them is by observing the dorsal furrow of the sixth somite. In this way, the present study aimed to verify the identity of F. brasiliensis and F. paulensis, using molecular and morphometric techniques. Additionally, it was also compared the population stocks of these species at three different regions along the coast of the Southeastern region, at São Paulo State. Extraction of genomic DNA, amplification of the COI gene (also used for DNA Barcoding system ), purification and sequencing were performed . The analyzes (haplotype network , analysis of genetic distance and dendrogram ) showed no genetic variability among the population stocks. F. brasiliensis and F. paulensis are valid species, the COI gene is efficient to separate such species, there is no genetic variation among the sampled sites for both species and the traditional characters do not allow the correct identification of both species juveniles. Considering only the molecular identity of the species, all variables measured for the traditional morphometry were significant in separating the groups analyzed. The discriminant analysis showed significant differences between the two species studied (p < 0.05). The geometric morphometric analysis of the carapace shape of individuals of F. brasiliensis and F. paulensis resulted in 16 relative warps and 2 uniform components. There were no differences in the shape of the carapace between the two species analyzed, both for males and females. Contrary to the expected, the structures identified by morphometric (traditional and geometrics) as significantly different among individuals were very subjective and they were not reliable for the identification of F. brasiliensis and F. paulensis. However, when analyzing the ...